Tindak Tutur Memohon dalam Bahasa Jepang (Irai): Analisis Skenario Drama Televisi Jepang Love Story Karya Eriko Kitagawa - Rita Susanti (Lingua Cultura, 2008)
The aim of this article was to know the social and cultural factors in the speech acts regarding requests in Japanese. Data were taken from the Japanese drama entitled Love Story. Analysis was done qualitatively by identifying, classifying, and explaining. The result indicated that there were three factors influencing the speech acts of requests in Japanese, those are the situation; the relationship between the speaker and the hearer; and the third is the social status, social interaction, and age. It is concluded that the speech does not mainly concern that the meaning should be easily understood but it also has to consider the socio cultural factor of the spreaker.